Answer:
y - 4 = 3(x- (-1) ---> y-4 = 3(x+1)
Step-by-step explanation:
y - 4 = 3(x + 1)
y - 4 = 3x + 3
y = 3x + 7
then plug in (-1,4)
4 = 3(-1) + 7
4 = -3 + 7
4 = 4
Point slope form looks like:
y - y₁ = m(x - x₁)
Answer:
x = – ⅓
Step-by-step explanation:
The solution to the expression can be obtained as follow:
–3.1x + 7 – 7.4x = 1.5x – 6(x – 3/2)
Clear bracket
–3.1x + 7 – 7.4x = 1.5x – 6x + 9
–3.1x – 7.4x + 7 = –4.5x + 9
–10.5x + 7 = –4.5x + 9
Collect like terms
–10.5x + 4.5x = 9 – 7
–6x = 2
Divide both side by –6
x = 2 / –6
x = – ⅓
Thus, the solution to the equation is –⅓
Answer: A)
The first one because the x don’t repeat
Answer:
(a) Increase the differences between the sample means this will increase the Numerator.
(b) Increase the sample variances will increase the denominator.
Step-by-step explanation:
F Ratio = Variance between treatments/ Variance within treatments.
Here,
(a) Increase the differences between the sample means:
- Will increase the Numerator and
- Size of the F-ratio would increase
(b) Increase the sample variances:
- Will increase the denominator and
- Size of the F Ratio would decrease.
Can you please please give me more information please thank you